Synthesis, Characterization and Biological Activities of new Nano Schiff bases Composites - M. Mohammed, Akhlas; Sultan, Maha T. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
New nano composites containing Schiff bases have been synthesized and presented in this paper. All compounds have been categorized through FT-IR and some of them by H-NMR spectroscopy. The antibacterial performance of the prepared compounds has been investigated according to the agar diffusion method. The compounds (P1,P2,C1, and C2) have shown, in general,  significant inhibition against bacterial.